Evaluasi Sistem Penyaliran Tambang Untuk Mendapatkan Sistem Penyaliran Ideal Tahun 2020 di Pit 1 Utara Bangko Barat, Jobsite TJMO, PT. Satria Bahana Sarana, Tanjung Enim, Sumatera Selatan - Ichsandhiyoni Ichsandhiyoni; Murad Murad (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT. Satria Bahana Sarana is a contractor company engaged in coal mining services located in Bangko Barat, Muara Enim district, South Sumatra province. PT Satria Bahana Sarana carries out the mining process using the open pit method. This method will cause the formation of a large basin so that it is very potential to become a water storage area. Based on field observations, there are many puddles of water around the mining front and haul roads, which can disrupt the mining process. Based on the analysis of rainfall data for 2010-2019, the planned rainfall was 482.82 mm/ day, with a return period of 2 years of rain. The method of solving the problem is done by analyzing several alternative solutions to problems related to handling the flow of water entering the pit, namely alternative I, a diversion channel that can minimize runoff discharge by 7,669 m3 / second. Alternative II for pump optimization of 6 units to compensate for the existing sump dimensions. Alternative III optimal sump dimensions to accommodate the total water discharge with a maximum volume 16,290 m3 . Based on the analysis of the three alternatives, an effective and efficient alternative I, with the estimated cost of Rp. 54,352,224.00.Keywords: Sistem Penyaliran Tambang, Catchment Area, Pompa, Sump, dan Saluran Terbuka